PENGARUH BIAYA PRODUKSI DAN BIAYA KUALITAS TERHADAP PENJUALAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI TAHUN 2021-2023 - Rosyida, Putri Adnani; Handayani, Alberta Esti (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study examines the impact of production costs and quality costs on sales in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The background of this research is based on the importance of efficient cost management in maintaining the company’s competitiveness. This study aims to analyze the impact of these two variables on sales. Method: This research employs a quantitative approach, using documentation methods to gather data from companies' annual financial statements. Result: The analysis indicates that both production and quality costs have a significant effect on sales, both simultaneously and partially. These findings suggest that efficient cost management can drive sales growth. Therefore, this research makes meaningful contributions to companies in helping them develop more effective business strategies. Keywords: Production Costs, Quality Costs, Sales, Manufacturing Companies, Indonesia Stock Exchange